Joie : a Parisian's guide to celebrating the good life - Aki, Ajiri (Clarkson Potter/Publishers, 2023)
"A joyful, aspirational, and approachable guide to embracing life the Parisian way, from American expat and founder of the French lifestyle brand Madame de la Maison. The French are known for their joie de vivre-celebrating the little things in life-a philosophy Ajiri Aki has embraced over the past ten years of living in Paris. Nigerian American Aki fell in love with Paris on her first brief visit there (only a single day) while in college. With a background in fashion and having earned a master's degree in decorative arts, it wasn't until she moved to Paris full time that she began to absorb lessons from the French: finding beauty in simple things every day, decorating with fresh flowers and flea market finds, taking time to find the best ingredients for a dish and gathering with loved ones around the table to share a meal or a glass, and perhaps most importantly, learning how to "être" - or just be. In this beautifully photographed volume of everything French, Aki shares all she's learned living in Paris, from hosting a perfect apéro (happy hour) to becoming a leisure-loving flâneur (loafer) in your own town, to how to find and celebrate joie de vivre. Explore all the prettiest Parisian cafes, plan a multi-course dinner party, learn how to properly loaf like the French, who work to live-rather than live to work-and allow yourself to slow down and find beauty and joyful moments all around you. With lush photographs of Paris's diverse landscape of food, people, culture, and architecture, Joie makes you eager to book your next trip to the City of Lights and to create that magic no matter where in the world you are"--